Evening - Minot, Susan (Knopf, 1998)
A woman dying of cancer relives a weekend with the man of her dreams. For Ann Lord, who subsequently married three times, nothing equalled the passion she felt for her first love, a doctor from the Korean War whom she lost to another woman.